Obsessive passion, opportunity recognition, and entrepreneurial performance: The dual moderating effect of the fear of failure - Tu, Yuqi; Hao, Xiling; Rosak-Szyrocka, Joanna; Vasa, László; Zhao, Xin (Frontiers in Psychology, 2023)
A strong inclination toward an important or preferred activity is a critical factor that drives individual to engage in corresponding activities. This study focuses on how entrepreneurs, influenced by obsessive passion, are motivated to put great effort into taking advantage of business opportunities and accomplishing entrepreneurial goals. By using SPSS and AMOS tools to analyze the multi-source questionnaire of 208 entrepreneurs, the research results show that obsessive passion can promote entrepreneurial performance and opportunity recognition plays a mediating role. In addition, endogenous and exogenous fear of failure play different moderating roles in the effect of obsessive passion on opportunity recognition. The research conclusion deepens the theoretical understanding of entrepreneurial passion, opportunity recognition, and fear of failure at a more subtle level.